2000
DOI: 10.1152/ajpcell.2000.279.5.c1665
|View full text |Cite
|
Sign up to set email alerts
|

β-Adrenergic receptor/cAMP-mediated signaling and apoptosis of S49 lymphoma cells

Abstract: beta-Adrenergic receptor (betaAR) activation and/or increases in cAMP regulate growth and proliferation of a variety of cells and, in some cells, promote cell death. In the current studies we addressed the mechanism of this growth reduction by examining betaAR-mediated effects in the murine T-lymphoma cell line S49. Wild-type S49 cells, derived from immature thymocytes (CD4(+)/CD8(+)) undergo growth arrest and subsequent death when treated with agents that increase cAMP levels (e.g., betaAR agonists, 8-bromo-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
72
2

Year Published

2003
2003
2009
2009

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(78 citation statements)
references
References 36 publications
4
72
2
Order By: Relevance
“…8-Cl-cAMP, 8-Br-cAMP, Bt 2 -cAMP and 8-CPT-cAMP), only CPT-cAMP acts purely as a cyclic nucleotide, having no effect on S49 kin Ϫ but strongly inhibiting growth of S49 WT cells (16). We found that 8-CPT-cAMP promoted apoptosis in WT but not kin Ϫ S49 cells in a time-dependent fashion, akin to that of another cAMP analog, 8-Br-cAMP (8), with a prominent increase in apoptosis after 24 h (Fig. 1A).…”
Section: -Cpt-camp Acts Via Pka To Increase Caspase-3 Activity and Imentioning
confidence: 57%
See 4 more Smart Citations
“…8-Cl-cAMP, 8-Br-cAMP, Bt 2 -cAMP and 8-CPT-cAMP), only CPT-cAMP acts purely as a cyclic nucleotide, having no effect on S49 kin Ϫ but strongly inhibiting growth of S49 WT cells (16). We found that 8-CPT-cAMP promoted apoptosis in WT but not kin Ϫ S49 cells in a time-dependent fashion, akin to that of another cAMP analog, 8-Br-cAMP (8), with a prominent increase in apoptosis after 24 h (Fig. 1A).…”
Section: -Cpt-camp Acts Via Pka To Increase Caspase-3 Activity and Imentioning
confidence: 57%
“…11 and 25), the precise determinants of cAMP-promoted cell death are poorly understood. Previous studies in the S49 cell system have documented that cell death promoted by cAMP analogs occurs via apoptosis (8) and that apoptosis and G 1 growth arrest are independent events that occur in WT but not kin Ϫ cells (10,11), thus implicating activation of PKA in the apoptotic process. In the current studies we show that the cAMP analog 8-CPTcAMP increases phosphorylation of CREB and activates caspase-3, as well as promoting apoptosis in WT but not kin Ϫ S49 cells (Fig.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations